Pirani Score Difference in CTEV Patients Treated with Ponseti’s Serial Cast in RSUP dr. Mohammad Hoesin Palembang - Setiamanah, Davin Caturputra; Lubis, Nur Rachmat; Septadina, Indri Seta (Majalah Kedokteran Sriwijaya, 2020)
Congenital talipes equinovarus (CTEV) is a congenital deformity involving calcaneo-navicular complex. It is best understood with mnemonic CAVE which includes cavus, adduction, varus, and equinus of the foot. Ponseti’s method, the gold standard of treating CTEV, includes strapping and tapping technique, manipulation, serial casting, and functional therapy. The purpose of this study is proving that there is a significant Pirani score difference in CTEV patients treated with Ponseti’s serial casts. It is an observational study with time series design. Observation and evaluation to the CTEV patients were conducted during the period of August-December 2017 at The Orthopedics Clinic in RSUP dr. Mohammad Hoesin Palembang. All the data were analyzed with Wilcoxon test using IBM SPSS version 24. Total 14 CTEV feet were treated with Ponseti method. From all of the 7 patients, four were females (57.1%) and three were males (42.9%). Every patient had bilateral deformity and less than a year in age. Mean Pirani score of the study group after the second plaster cast were 3.78 ± 2.05 for the left feet and 4.07 ± 1.66 for the right feet. Mean post-treatment Pirani score of the study group, respectively left and right feet, were 0.57 ± 0.60 and 0.28 ± 0.39. Total 92% of the feet were treated successfully by Ponseti’s serial casts. There is a significant difference in Pirani score before and after the treatment of CTEV using Ponseti’s serial casts (p < 0.05).